An electrospun cellulose-based nanofiber piezoelectric membrane with enhanced flexibility and pressure sensitivity. Issue 14 (23rd March 2023) - Zhang, Minghao; Hu, Ke; Meng, Qingyu; Lan, Zhuyue; Shi, Shitao; Sun, Qingfeng; Zhou, Lei; Shen, Xiaoping
Abstract : An electrospun cellulose diacetate (CDA)–silica–lead zirconate titanate (PZT) hybrid nanofiber-based piezoelectric mat with superior homogeneity, flexibility, piezoelectricity and pressure sensitivity was prepared. Abstract : Real-time monitoring of human activities is of great significance for skill training and posture correction. Here, we design a cellulose derivative based electrospun nanofibrous piezoelectric mat with excellent flexibility and pressure sensitivity as a substitute for films from polyvinylidene fluoride (PVDF) and its derivatives. Silanol is introduced in the system containing rigid lead zirconate titanate (PZT) nanoparticles (NPs) as an inorganic amorphous phase to increase both the formability and flexibility. A flat nanofiber-based film with stuffed pores via tight nanofiber entanglement can be manufactured on a large scale by a facile two step method of electrospinning and compression processes. As a result, the flexible cellulose-based hybrid sensor exhibits linear, preeminent sensitivities (25 mV kPa −1 and 36.50 mV kPa −1 within 0–50 kPa and 0.06–0.12 MPa, respectively). On this basis, we demonstrate the sensor to real-timely fetch the hit location and contact force for table tennis training and to continuously track gestures such as typewriting and walking. This work provides a new prospect for artificial intelligence electronics toward smart sports, clothing and shoes.